Flipped Classroom for Doctoral Students: Evaluating the Effectivness - K. N. Volchenkova (Moscow Polytechnic University, 2019)
The demand of Industry 4.0 for creative researchers able to adopt to the changing world and think out of the box puts forward the question of education technologies used to prepare such specialists. Though many new education technologies have appeared recently their effectiveness has not yet been proved to be introduced into tertiary education in a large scale. The author presents the evidence for the flipped classroom technology effectiveness. The paper describes the rationale and content of the doctoral program course "English for Research Purposes" delivered using flipped classroom approach. The course was piloted in September-May, 2017/2018 academic year with 197 doctoral students participating. Both quantitative and qualitative evaluation of the flipped classroom was made. Direct education outcomes (students' scores at the end of the course and attendance rates) and indirect education outcomes (students' attitudes, perceptions, and feelings towards the course; students' empowerment and development in the course) were measured using analysis of variance with repeated measures and Likert Scale surveys. The results showed that a general increase in students' ratings of the effectiveness of the flipped classroom elements was observed during the course, the students' scores increased 11,3% in comparison with the results of the 2016/2017 academic year where a traditional approach was used. The results of the research can be used to modernize the education process of doctoral students' training based on flipped classroom technology both at the universities ofRussian Federationand at foreign universities.